Ancestral role of Pax2/5/8 in molluscan brain and multimodal sensory system development. (December 2015) - Wollesen, Tim; Rodríguez Monje, Sonia; Todt, Christiane; Degnan, Bernard; Wanninger, Andreas
Abstract Background Mollusks represent the largest lophotrochozoan phylum and exhibit highly diverse body plans. Previous studies have demonstrated that transcription factors such asPax genes play important roles during their development. Accordingly, in ecdysozoan and vertebrate model organisms, orthologs ofPax2/5/8 are among others involved in the formation of the midbrain/hindbrain boundary, the auditory/geosensory organ systems, and the excretory system. Methods Pax2/5/8 expression was investigated byin situ hybridization during the development of representatives of the two major molluscan subclades, Aculifera and Conchifera. Results Compared to the investigated polyplacophoran and bivalve species that lack larval statocysts as geosensory organs and elaborate central nervous systems (CNS), cephalopods possess highly centralized brains and statocysts.Pax2/5/8 is expressed in regions where sensory cells develop subsequently during ontogenesis. Expression domains include esthetes and the ampullary system in polyplacophorans as well as the eyes of cephalopods. NoPax2/5/8 expression was observed in the less centralized CNS of bivalve, polyplacophoran, and gastropod embryos, thus arguing for a loss ofPax2/5/8 involvement in CNS development in these lineages. In contrast, Pax2/5/8 is expressed among others in brain lobes along the trajectory of the esophagus that divides the cephalopod brain. Conclusions Our results, along with those onOtx - andHox -gene expression, demonstrate that the cephalopod condition is similar to that in mouse and fruit fly, withOtx being expressed in the anterior-most brain region (except for the vertical lobe) and aPax2/5/8 expression domain separating theOtx -domain from aHox -gene-expressing posterior brain region. Thus, Pax2/5/8 appears to have been recruited independently into regionalization of non-homologous complex brains of organisms as different as squid, fruit fly, and mouse. In addition, Pax2/5/8 is expressed in multimodal sensory systems in mollusks such as the esthetes and the ampullary system of polyplacophorans as well as the eyes of cephalopods.Pax2/5/8 -expressing cells are present in regions where the future sensory cells such as the polyplacophoran esthetes are situated and hencePax2/5/8 expression probably predates sensory cell development during ontogeny. In mollusks, Pax2/5/8 is only expressed in derivatives of the ectoderm and hence an ancestral role in molluscan ectoderm differentiation is inferred.